Reviewing the Effectiveness of Educational Technologies in Enhancing Student Learning Outcomes - Jihan; Nur Iswantara; Erni Murniarti; Hepsi Nindiasari; Ira Arini (Global Writing Academica Researching and Publishing, 2023)
Technological developments have helped human life in various fields, including education. In practice, technology has a positive influence on student learning outcomes. This research will be carried out to see how effective the use of technology is for student learning outcomes. This research was conducted using a descriptive qualitative approach. The data used in this study comes from various research results and previous studies, which still have relevance to the content of this research. The study results then found that technology can assist educators in providing material to students. Then students can also be helped to understand the material delivered by the teacher through technology. Various uses of this technology prove the effectiveness of the use of technology to improve student learning outcomes. Therefore, educators, such as teachers, must use the right technology to carry out the learning process.